The Effect of Green Marketing Tools and Strategies on Consumers’ Purchase Intention in Food and Beverage Industry: A Case in Klang Valley, Malaysia - Khor, Wen Loon (2013)
The interaction between businesses and the environment has been an issue since the early of 1970s. Nowadays, consumers are becoming more environmentally responsible and some of them prefer a green product over a conventional one. In response to this, many businesses have produced green products to satisfy the consumers’ needs. Besides, they also have started to incorporate green marketing into their marketing strategies. They have developed variety tools and strategies to market their green products and some of them are like eco-brands, eco-ingredients, eco-labels, ecopackaging and green integrated marketing communications tools. However, their significant impacts on consumers’ green purchase intention are still uncertain and these have become the subject of some researches in recent years. On top of that, in Malaysia, like many other developing countries, not much attention was paid to environmental issue and this topic has been under-researched. Hence, this research aims to examine how the green marketing is used by food and beverage industry to influence the green purchase intention of consumers in Klang Valley, Malaysia. Based on the literature review that was available, a framework was developed and this research was conducted through quantitative approach. The data was collected through questionnaires and analyzed by using Smart PLS and SPSS 20.0 software’s with multiple kinds of tests such as structural equation modeling and Mann-Whitney. The empirical findings of the study suggest that eco-packaging, eco-brands, eco-ingredients and eco-label are the green marketing tools and strategies that will influence the consumers’ green purchase intention of food and beverage. The results also suggest that female consumers are more environmentally friendly compare to male as it is proven they tend to respond more positively towards eco-brands’ products.